REAKSI PASAR TERHADAP KEMENANGAN JOE BIDEN DALAM PEMILIHAN UMUM PRESIDEN AMERIKA SERIKAT TAHUN 2020 DI EMERGING MARKET - Rani Dewi, Anak Agung Ayu Mas Radha; Wiksuana, I Gst. Bgs. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
This study aims to determine the market reaction to the events of Joe Biden's victory in the United States presidential election in 2020, especially in the emerging market, namely Indonesia and the Philippines. This research uses an event study approach with a 11 day event window. The research sample is based on purposive sampling as many as 22 multinational companies that are members of the LQ45 Index, and 14 multinational companies that are members of the PSE Composite Index. The hypothesis test used in this research is One Sample t-test and Paired Sample t-test. The results of this study indicate (1) There is a market reaction in the form of significant abnormal returns around events in Indonesia and the Philippines (2) There is no difference in abnormal returns before and after events, both in Indonesia and the Philippines. The results of this study can show that the capital market in Indonesia and the Philippines can be in the form of an informational semi-strong form of efficiency market. The results of this study can be used as a consideration for investors in calculating the risk of non-economic issues that affect the capital market.